The Woman in the Natural Sciences: A History of Confrontations and Conquests (Research, Society and Development, 2019)
In the contemporary world, many approaches have been focused on gender equality, reinforcing the need to expand educational and professional opportunities for women, so that it is no longer limited to the roles assigned to them, as wife, mother and housewife . However, how to deconstruct a patriarchal and exclusionary system that has so much contributed to impede the advancement of women in society? Considering the relevance of the subject in question, this article aims to discuss the prejudices directed at women in society, highlighting the confrontations experienced by those who seek or sought to act in the scientific area, as a space initially represented as masculine. The approach is done through a bibliographical research, based on the concept of gender for the purpose of understanding the discriminatory social process to which it is exposed, together with the maintenance of inequalities between the sexes, which is still corroborated in the present day to hinder the women's access to science. Through the studies and data presented, it is concluded that despite the increasing visibility and respective insertion of women in science, there is still a great struggle for the conquest of women's space in scientific careers.